Responsiveness Mediates Accountability and Transparency for Stakeholder Participation in Pondok Pesantren: Responsiveness,Accountability, Transparency, Participation, Pondok Pesantren - Munir Is’adi; Abdur Rakhman Wijaya (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study investigates how perceived accountability (PA) and perceived transparency (PT) shape stakeholder participation (PP) in Pondok Pesantren, with perceived responsiveness (PR) as a mediator. Using a quantitative, causal design and Partial Least Squares-Structural Equation Modelling (PLS-SEM), data were collected from 89 stakeholders (students, parents/ guardians, alumni, local community, and donors) across several Pesantren in Jember. The measurement model shows strong reliability and validity (CR = 0.922—0.964; AVE > 0.50; all loadings > 0.70; VIF < 5). The structural model explains 81.5% of the variance in participation (R-square = 81.5%) and 77.3% in responsiveness (R-square = 0.773), with high predictive relevance (Q-Square PP = 0.595; Q-Square PR = 0.558). Key paths indicate that PR → PP is the strongest predictor (O = 0.539; p < 0.001), PT → PR (O = 0.331; p = 0.0012) are significant. Mediation tests confirm full mediation of PR in the PA → PR (O = 0.313; p = 0.002) and partial mediation in the PT → PP link (O = 0.178; p = 0.026). The findings suggest that accountability and transparency foster participation when they are experienced as responsiveness, offering a governance pathway aligned with amanah, ihsan, and shura..